Chemical shift–based prospective k‐space anonymization. Issue 2 (6th August 2020) - Mattern, Hendrik; Knoll, Martin; Lüsebrink, Falk; Speck, Oliver
Abstract : Purpose: Publicly available data provision is an essential part of open science. However, open data can conflict with data privacy and data protection regulations. Head scans are particularly vulnerable because the subject's face can be reconstructed from the acquired images. Although defacing can impede subject identification in reconstructed images, this approach is not applicable to k‐space raw data. To address this challenge and allow defacing of raw data for publication, we present chemical shift–based prospective k‐space anonymization (CHARISMA). Methods: In spin‐warp imaging, fat shift occurs along the frequency‐encoding direction. By placing an oil‐filled mask onto the subject's face, the shifted fat signal can overlap with the face to deface k‐space during the acquisition. The CHARISMA approach was tested for gradient‐echo sequences in a single subject wearing the oil‐filled mask at 7 T. Different fat shifts were compared by varying the readout bandwidth. Furthermore, intensity‐based segmentation was used to test whether the images could be unmasked retrospectively. Results: To impede subject identification after retrospective unmasking, the signal of face and shifted oil should overlap. In this single‐subject study, a shift of 3.3 mm to 4.9 mm resulted in the most efficient masking. Independent of CHARISMA, long TEs induce signal decay and dephasing, which impeded unmasking. Conclusion: To our best knowledge, CHARISMA is the first prospective k‐space defacing approach. With proper fat‐shift direction and amplitude, this easy‐to‐build, low‐cost solution impaired subject identification in gradient‐echo data considerably. Further sequences will be tested with CHARISMA in the future.